RAMS of Railway Infrastructure A Review - Rachmad Indrakusuma; Yunendar Aryo Handoko (Jurnal Teknologi dan Manajemen, 2023)
RAMS is crucial for assuring the correct functioning of railway transportation, which is a critical mode of transit for both passengers and products. The paper provides a comprehensive overview of the components and theory of RAMS and highlights commonly used methods in each discipline. The benefits and sustainability of RAMS and complementary disciplines such as Life Cycle Cost (LCC) are also discussed. The integration of RAMS and LCC can provide railway companies and passengers with numerous benefits. The RAMS methodology consists of four essential components: availability, maintainability, safety management, and reliability. While implementing RAMS, businesses must consider potential obstacles such as limited data and resources. To foster an environment conducive to RAMS implementation, businesses need government and industry support. Future research must be conducted on optimizing assets across the entire railway system, and RAMS and LCC requirements must be digitized within the asset system.